IMPLEMENTASI STRATEGI SEGMENTING, TARGETING DAN POSITIONING DI LAENA TOUR PEKANBARU - Erna Yunita; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently the competition in tourism industry is getting tighter. One of the tour and travelcompanies which is named Laena Tur Pekanbaru also faces an intense competition in Pekanbaru withvarious competitors bith online company and fellow tour and travel company. Therefore, this studyaims to describe the marketing strategy (Segmenting, Targeting and Positioning) in Laena tourPekanbaru and describe its implementation. The research’s data was collected through interviews withthe management including employees. The result of research shows that Laena Tour Pekanbaru is usingsegmenting base such as geografic segmenting, demografic segmenting, psikografic segmenting. Interms of targeting, Laena Tour Pekanbaru uses determination different target market and focus onumrah and haji product. In terms of posiyioning, Laena Tour Pekanbaru uses base price, quality andcompetitor, the company also do the steps in determination of market position.Keywords: Segmenting, Targeting, Positioning, Tour and Travel